Experimental Vaccines against Chagas Disease: A Journey through History - Olivia Rodríguez-Morales; Víctor Monteón-Padilla; Silvia C. Carrillo-Sánchez; Martha Rios-Castro; Mariana Martínez-Cruz; Alejandro Carabarin-Lima; Minerva Arce-Fonseca (Journal of Immunology Research)
Chagas disease, or American trypanosomiasis, which is caused by the protozoan parasite Trypanosoma cruzi, is primarily a vector disease endemic in 21 Latin American countries, including Mexico. Although many vector control programs have been implemented, T. cruzi has not been eradicated. The development of an anti-T. cruzi vaccine for prophylactic and therapeutic purposes may significantly contribute to the transmission control of Chagas disease. Immune protection against experimental infection with T. cruzi has been studied since the second decade of the last century, and many types of immunogens have been used subsequently, such as killed or attenuated parasites and new DNA vaccines. This primary prevention strategy appears feasible, effective, safe, and inexpensive, although problems remain. The objective of this review is to summarize the research efforts about the development of vaccines against Chagas disease worldwide. A thorough literature review was conducted by searching PubMed with the terms “Chagas disease” and “American trypanosomiasis” together with “vaccines” or “immunization”. In addition, reports and journals not cited in PubMed were identified. Publications in English, Spanish, and Portuguese were reviewed.